Management practice in safety culture and its influence on workplace injury: An industrial study in Malaysia - Ali, Hassan; Chew Abdullah, Nor Azimah; Subramaniam, Chandrakantan (Emerald Group Publishing Limited, 2009)
Purpose– The purpose of this paper is to examine to what extent management practices in safety culture are effective in reducing workplace injuries.Design/methodology/approach – Management practices are an important component of an organization’s safety climate.The study was conducted in a major industrial zone in Malaysia.The management practices examined in this study were reward, training, management commitment, communication and feedback, hiring practices, and employee participation. In total, 68 companies participated in this study; the injury data provided by the companies were for three years and 24 musculoskeletal injuries were examined.Findings– The multiple correlation was at 0.43 and the R2 was 0.19. A significant linear relationship between management practices subscale and injury rates was obtained (F¼2:28,p¼0:14). Rewards, management commitment, feedback and selection were found to reduce injury rates.However, only feedback (t¼22:98) and employee participation (t¼2:01) were significantly predicting the injury rates. Implementing good management practices does reduce injury rates.Research limitations/implications– Nevertheless, a positive relationship for participation with injury rates suggests that a re-examination of these practices is necessary, as it may not be effective in reducing injury rates.Practical implications – It may be posited that although frequency counts of injuries in the workplace do provide some indication of the extent of workplace injury; nevertheless they do not provide a true account of the severity of these injuries.Originality/value – This paper presents empirical findings on the relationship between management practices and injury rates in the industrial sector in Malaysia